1972
DOI: 10.1111/j.1471-4159.1972.tb05117.x
|View full text |Cite
|
Sign up to set email alerts
|

THE PATTERN OF METHYLATION OF RNA IN PERIPHERAL NERVE OF THE CHICK DURING DEVELOPMENT1

Abstract: The pattern of the methylation of RNA was investigated in organ cultures of the sciatic nerve of the chicken. Nerve tissue from 14‐day embryos, 17‐day embryos and 3‐day‐ old chicks was incubated with [methyl‐3H]methionine or with [2‐14C]uridine and [methyl‐3H]methionine simultaneously for various periods of time. Subsequently, RNA was extracted from the tissues and the purified preparations were fractionated by polyacrylamide gel electrophoresis. The electrophoretic patterns of the rapidly labelled RNA changed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Thus, tissue of one developmental stage exposed to tissue of another stage still showed the characteristic shift in the apparent size distribution of poly(A)+ RNA. The change in the size of the poly(A)+ RNA as well as in the electrophoretic properties of crude rapidly labeled RNA of the chick nervous system during development is in agreement with previous studies done on sciatic nerve Mezei and Hu, 1972). Berthold and Lim (1976b) reported that the nuclear and cytoplasmic polyadenylated RNA species of young rat brain are also larger than their corresponding adult counterparts.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, tissue of one developmental stage exposed to tissue of another stage still showed the characteristic shift in the apparent size distribution of poly(A)+ RNA. The change in the size of the poly(A)+ RNA as well as in the electrophoretic properties of crude rapidly labeled RNA of the chick nervous system during development is in agreement with previous studies done on sciatic nerve Mezei and Hu, 1972). Berthold and Lim (1976b) reported that the nuclear and cytoplasmic polyadenylated RNA species of young rat brain are also larger than their corresponding adult counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, great caution should be exercised in interpreting data concerning differential synthesis of various RNA species in the absence of specific knowledge about the behavior of their precursor With the availability of affinity chromatography for the isolation of poly(A)+ RNA it has become possible to compare the polyacrylamide gel electrophoretic patterns of this RNA with those obtained previously for total rapidly labeled RNA of the identical developmental stage. Thus, if a sizable amount of poly(A)+ RNA could be obtained from embryonic and post-hatching tissues, and if the average size distribution of the poly(A)+ RNA was similar to that found previously for the crude rapidly labeled RNA of sciatic nerve and brain of chicks Mezei and Hu, 1972), one could conclude that at least part of the rapidly labeled RNA observed in these tissues was poly(A)-containing mRNA or hnRNA. The results of these investigations have borne out these expectations (Table 3).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations